Formulation and in vitro assessment of indomethacin submitted to solid dispersion for the purpose of enhancing its dissolution - Razooqi, Khatab Duraid; Hameed, Ghaidaa S.; Albakaa, Ali R. M. (Pharmakeftiki, 2025)
Indomethacin (IND), a nonsteroidal anti-inflammatory drug, is widely employed in the pharmaceutical sector for its analgesic, anti-inflammatory, and antipyretic properties. However, IND exhibits poor dissolution in gastrointestinal tract fluids, leading to limited bioavailability. Solid dispersion (SD) is a well-established and widely adopted strategy for enhancing drug dissolution. This study aimed to formulate and evaluate, in vitro, the SD technique for improving IND dissolution. IND-based SDs were prepared using the solvent evaporation method and three distinct polymers: Soluplus®, polyvinylpyrrolidone K30 (PVP K30), and hydroxypropyl methylcellulose E5 (HPMC E5). The resulting SDs were assessed for in vitro drug release and subjected to solid-state characterization. Among the formulations, the Soluplus®-based SD demonstrated superior performance, achieving 100% drug release within 2 h, compared to 74.75% and 53.00% release from PVP K30 and HPMC E5-based SDs, respectively. Solid-state analyses confirmed complete amorphization of IND within the SD matrix, with no evidence of physicochemical incompatibility. In conclusion, the Soluplus®-based SD prepared via solvent evaporation represents an effective approach for enhancing the dissolution profile of IND.